Carcinoma in a Girolando Cow - Treatment with Radical Exeresis and Vulvoplasty - Carneiro Fagundes Lino, Daniel; Lauar Fagundes Lino, Jéssyca; Junqueira Borges, José Renato; Ximenes, Fábio Henrique Bezerra; Lopes Câmara, Antônio Carlos (Acta Scientiae Veterinariae, 2024)
Background: Squamous cell carcinomas (SCC) are malignant tumors of the spinous layer of the cellular epithelium. The main risk factor associated with its formation is solar radiation, therefore, despite appearing anywhere on the body, it is more commonly observed in depigmented regions, mainly mucocutaneous junctions. In small lesions, the use of hyperthermia, cryotherapy, and surgical excision associated to topical (mitomycin C and 5-fluouracil) or intralesional (interleukin-2, BCG and cisplatin) drugs is advisable. In large and invasive lesions, associating surgical excision with other treatments (multimodal approach) is recommended. The present study aimed to report the radical surgical excision followed by vulvoplasty in the treatment of extensive vulvar SCC in a Girolando cow. In addition, the successful use of a waterproof surgical drape, aiming to reduce surgical site contamination in the postoperative period, is also reported. Case: A 6-year-old Girolando cow, weighing 400 kg, was referred to the Veterinary Hospital care after a clinical evolution of 5 months. At physical examination, vital parameters were within the physiological parameters for cattle. Dermatological evaluation revealed an ulcerated tumor-like lesion with irregular shape and firm consistency affecting both vulvar lips, reaching approximate dimensions of 10 x 15 cm. Two 8 mm punch biopsies were performed at the borderline junction between affected tissue and healthy vulvar skin. Histological examination confirmed the diagnosis of keratinizing SCC. Therefore, the cow was submitted to radical surgical excision followed by vulvoplasty. After removal of the bilaterally affected tissue, the dead space was obliterated by simple separated size 2-0 polyglactin stitches. Dermorrhaphy was accomplished by separated size 0 captonated Wolf pattern with nylon thread. In order to reduce post-surgical contamination, we opted for fixing a waterproof surgical drape above the dorsal commissure of the vulva with size 0 nylon continuous suture. Despite surgical margins involvement, no recurrences were reported within 6 months after the surgical procedure. Discussion: Hereford and Holstein breeds, as well as their crosses, due to their hypopigmented skin, are more prone to develop SCC. In the present report, it is believed that the main risk factor was high sun exposure, since the herd was raised extensively, and the Girolando cow had vulvar areas of depigmentation. Despite the epidemiology and clinical findings being suggestive of SCC, histological confirmation is essential, as this is an invasive neoplasm and its histological characteristics allow the differentiation from other types of vulvar neoplasms, helping in the treatment choice and determining prognosis. In cases of very extensive, infiltrative and poorly differentiated neoplasms, radical surgical treatment is recommended, but there is great concern about recurrences. Therefore, the earlier the surgical intervention, the better the prognosis, since the SCC tends to have invasive growth, which increases the risk of compromising the surgical margins by tumor cells. Additionally, the use of a waterproof surgical drape fixed in the perineal region provided less contamination of the surgical site. In this case, healing occurred without major complications, and hospital discharge occurred on the 18th postoperative day. Thus, in the present report, radical excision followed by vulvoplasty in the treatment of SCC in the Girolando cow was a successful approach. We reiterate the use of waterproof plastic surgical drapes in the postoperative period of genital surgeries in cows, given its low cost and adjuvant action in reducing post-surgical complications, such as infections and dehiscence. Keywords: bovine, squamous cell carcinoma, vulvar neoplasm, waterproof surgical drape. Título: Carcinoma em vaca Girolando - tratamento com exérese radical e vulvoplastia Descritores: bovino, campo cirúrgico impermeável, carcinoma de células escamosas, neoplasia vulvar.